Synthesis and characterization of alumina nanofiber filled poly ether ether ketone (PEEK) - Tg Mahizatulazwa, Tg Kamaruddin (2012)
This studies aims to understand the effects of alumina nanofiber filled Poly ether ether ketone (PEEK) on the nanocomposite physical-chemical,thermal and crystallization behaviour.Alumina nanofiber has been prepared by sol gel method. The addition of alumina nanofiber into PEEK was carried out via in-situ polymerization to obtain homogenous materials.The nanocomposites were prepared by dispersing the fibre in solvent and then undertaking the in-situ synthesis of PEEK.Composite materials with 1 wt %, 2.5 wt % and 5 wt % of alumina nanofiber have been successfully prepared by dispersing the alumina nanofiber in sulfolane as solvent and upon sonication for 30 minutes. Due to the small size of the nanoflilers, high magnifications are required to observe the dispersion of the alumina nanofibers in PEEK matrix.Transmission electron micrograph (TEM) and field emission scanning electron micrographs (FESEM)indicated excellent dispersion and interactions between PEEK matrix with the adding of alumina nanofibers. Differential scanning calorimeter studies show changes in melting and crystallization point and degree of crystallinity with different loading of alumina nanofiber.The result also indicated that alumina nanofiber serves as nucleating agentsin PEEK composites.The X-Ray diffractogram (XRD) data indicated that the crystallinity of the PEEK composites was highest with 1 wt % alumina nanofiber.The thermogravimetry analysis (TGA), shows that the thermal stability for 1 wt % alumina nanofiber-PEEK composites was enhanced compared to that of pure PEEK.